The a to Z of U. S. Diplomacy from World War I Through World War II - Folly, Martin; Palmer, Niall (Rowman & Littlefield Publishers, 2010)
The period from the outset of World War I to the end of World War II was among the most significant in the history of the United States. Twice it was drawn into "foreign entanglements"— wars it initially thought were no concern of its own and of which it tried to steer clear—only to realize that it could not stand aside. With each one, it geared up in record time, entered the fray massively, and was crucial to the outcome. Each war tested the American people and their leaders, and in each case the country came out of the conflagration stronger than before-and even more important-yet stronger relative to other countries than it had ever been. This was the period when the United States became a world leader. The A to Z of U.S. Diplomacy from World War I through World War II relates the events of this crucial period in U.S. history through a chronology, an introductory essay, and over 600 cross-referenced dictionary entries on key persons, places, events, institutions, and organizations.